2016
DOI: 10.1021/acs.jnatprod.6b00158
|View full text |Cite
|
Sign up to set email alerts
|

Ceylonamides A–F, Nitrogenous Spongian Diterpenes That Inhibit RANKL-Induced Osteoclastogenesis, from the Marine Sponge Spongia ceylonensis

Abstract: Seven new spongian diterpenes, ceylonamides A-F (1-6) and 15α,16-dimethoxyspongi-13-en-19-oic acid (7), were isolated from the Indonesian marine sponge Spongia ceylonensis along with eight known spongian diterpenes, 8-15. Compounds 1-6 were determined to be nitrogenous spongian diterpenes. The isolated compounds were examined for the inhibition of RANKL-induced osteoclastogenesis in RAW264 macrophages. Ceylonamide A (1) exhibited the most potent inhibitory activity with an IC50 value of 13 μM, followed by ceyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 14 publications
(37 reference statements)
0
20
0
Order By: Relevance
“…Therefore, the current primary issues in marine conservation, such as the loss of biodiversity through over-exploitation and habitat degradation, can be overcome. Additional information can be found in the Supplementary Materials [95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150,151,152,153,154,…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the current primary issues in marine conservation, such as the loss of biodiversity through over-exploitation and habitat degradation, can be overcome. Additional information can be found in the Supplementary Materials [95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150,151,152,153,154,…”
Section: Discussionmentioning
confidence: 99%
“…Geodiataurine exhibited weak activity (IC 50 ¼ 8.5 mM) against A2058 melanoma cells but with no antibacterial effects. 454 Other diterpenoids, 949 and 950 (total syntheses also achieved), 455 especially based upon the ubiquitous spongian diterpene skeleton 951-962, [456][457][458] were isolated from Theonella, Dysidea, Spongia and Dendrilla sponges, all with varying activities. Several norscalarane 963-967 (ref.…”
Section: Spongesmentioning
confidence: 99%
“…The Electrospray Ionization Time of Flight Mass Spectrometry (ESI-TOF-MS) of 1 showed a quasi-molecular ion peak [M + Na] + at m/z 354, and the molecular formula was determined as C 20 H 29 NO 3 by high-resolution (HR)-ESI-TOF-MS. 1 H- and 13 C-Nuclear Magnetic Resonance (NMR) spectra of 1 showed the characteristic signals of terpenes, 3 methyl signals [δ H 1.19 (3H, s), δ C 22.4 (C-17); δ H 1.21 (3H, s), δ C 29.3 (C-18); δ H 0.89 (3H, s), δ C 14.7 (C-20)], 2 carbonyl carbon signals [δ C 177.4 (C-16) and δ C 183.8 (C-19)], and 2 olefin carbon signals [δ C 129.2 (C-13) and δ C 166.5 (C-14)]. In addition, NMR spectra of 1 were similar to those of ceylonamide F. 4,12 Marked differences in the chemical shifts of the carbon atoms in these compounds were observed at δ C 22.8 (C-12), δ C 129.2 (C-13), δ C 166.5 (C-14), δ C 45.6 (C-15), and δ C 177.4 (C-16) for 1 and at δ C 27.4 (C-12), δ C 154.1 (C-13), δ C 141.3 (C-14), δ C 176.4 (C-15), and δ C 49.2 (C-16) for 4 (Tables 1 and 2). Then, the Heteronuclear Multiple Bond Correlation (HMBC) correlations between δ H 2.05, 2.32 (H-12) and δ C 129.2 (C-13), δ C 177.4 (C-16); δ H 3.85, 3.95 (H-15) and δ C 129.2 (C-13), δ C 166.5 (C-14), δ C 177.4 (C-16); δ H 1.19 (H-17) and δ C 166.5 (C-14) indicated that the γ-lactam ring of 1 had the opposite orientation to that of 4 (Figures 1 and 2).…”
mentioning
confidence: 77%
“…13 On the other hand, the specific rotations of compounds 1 to 3 were also negative (−24, −23, and −32, respectively) and were similar to the reported specific rotations of ceylonamides A-F (−26, −29, −26, −38, −23, and −110, respectively). 12 The absolute stereochemistry of compounds 1 to 3 are illustrated in Figure 1. The absolute configuration of ceylonamide F ( 4 ) was also determined on the basis of the specific rotations of spongolactams.…”
mentioning
confidence: 99%